Writing as The Highest Level Of Civilization (An Analysis Study on the Writing History and Language Component) - Sofian Hadi; Ismiati I (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This paper written with an intention of exploring point of view on how writing being the fundamental level of civilization. By recognizing the writing element since the history, marked the developing and advancing level of human being in utilized the facilities to build communication each other through skills. On the other hand, this paper is library research as the for the analysis study related to the subject or component of language writing. Such as history (tarÃ®kh) as a sign of the birth of the historical era, which ended prehistoric times, marked by the development of writing, language skill components. Further, the relationship between writing and speaking, the relationship between writing and reading. The last part will be discussed about writing as a reflection of listening, speaking and reading. In conclusion, writing gave numerous functions for communicating practice through the four skills, listening, speaking, reading and writing. As the result, writing is the elementary skill to be sharpened and practiced through the exercise and the culmination will be the beneficial for the advanced of human civilization.Â